Hubungan Intensitas Berdzikir dengan Kebermaknaan Hidup Santri Kalong - Ahmad Maujuhan Syah (Conseils : Jurnal Bimbingan dan Konseling Islam, 2021)
The aim of this research is discussing the relation between dzikrullah intensity with life meaning of the scholars of kalong in Darur Rohman Sendangagung dormitory, Lamongan. This research uses quantitative method. Research variables are measured by using the scale of life meaning and dzikrullah intensity. The subjects of this research are 60 scholars of kalong in Darur Rohman dormitory. The gotten data is analyzed by using product moment analysis. The result of this analysis shows that dzikrullah intensity variable are related very significantly with the life meaning (sig. : 0,001)